Peran Penting Orangtua dalam Mendidik Anak di Society 5.0 - Muhammad Nadhil Mawarid; Aji Wibawa (Universitas Ngeri Malang, 2022)
Parents are leaders for children in a family. The existence of children's education in a family is essential and this falls into one of the parents' responsibilities. The advanced development of human life in the field of technology provides various reliefs and various opportunities that can be utilized, but still comes with its own drawbacks and obstacles. As human life develops towards Society 5.0, the biggest challenge comes from family members, especially parents, who are less competent and less knowledgeable about raising children. Therefore, this issue will be discussed further in this article by utilizing the qualitative research method of literature study. The results of the literature study show that in welcoming the development of human life towards Society 5.0, it is necessary to have individuals who can: think critically, have high curiosity, think openly, be creative and become problem solvers. This is due to the conditions and situations of Society 5.0 where the flow of information exchange occurs very quickly and easily as well as disruptive and fluctuating conditions. Orangtua adalah figur pemimpin bagi anak dalam sebuah keluarga. Adanya pendidikan anak dalam sebuah keluarga sangatlah esensial dan hal ini jatuh menjadi salah satu tanggung jawab orangtua. Majunya perkembangan kehidupan manusia di bidang teknologi memberikan beragam keringanan dan sekian kesempatan yang dapat dimanfaatkan, namun tetap dengan kekurangan dan hambatannya tersendiri. Seiring dengan berkembangnya kehidupan manusia menuju Society 5.0, tantangan terbesar justru datang dari anggota keluarga, terutama orang tua, yang kurang kompeten dan kurang berpengetahuan tentang membesarkan anak. Oleh karena itu, isu ini akan dibahas dengan lebih lanjut dalam artikel ini dengan memanfaatkan metode penelitian kualitatif studi literatur. Hasil studi literatur menunjukkan bahwa dalam menyambut perkembangan kehidupan manusia menuju Society 5.0, diperlukan adanya individu yang dapat bersikap: berpikir kritis, rasa ingin tahu yang tinggi, berpikir terbuka, kreatif dan menjadi problem solver. Ini disebabkan dengan kondisi dan situasi Society 5.0 di mana arus pertukaran informasi terjadi dengan sangat cepat dan mudah serta keadaan yang bersifat disruptif dan fluktuatif.